EFFECTIVE MANAGEMENT OF HUMAN CAPITAL AS THE BASIS FOR THE DEVELOPMENT OF NATIONAL ECONOMY - K.M. Zhumaxanova,; G.S. Smagulova,; R.G. Yessenzhigitova, (Academic Journal of Physical and Chemical Sciences, 2019)
One of the priorities of the institutional and structural reforms implemented by Kazakhstan in the years of its independence is the formation of systemic conditions for the development and growth of the country's human capital. The issue of the development of human capital has always been in the focus of both conceptual documents that determine the development strategy of the state and society, and real actions undertaken by the political leadership of the country. Entering the forefront of human capital is one of the modern global trends. Human capital is the main economic resource of the 21st century, increasing the country's GDP, which has become the main productive and social factor in the development of the economy of the Republic of Kazakhstan. The transition of the Republic of Kazakhstan to a market economy raised the question of the need to create effective systems that ensure high quality human resources, the peculiarity of which is that: - firstly, the more people are involved in professional activities, the more they accumulate life and professional experience, the less time they need for a high-quality solution of professional tasks, the greater their value; - secondly, this is the most complex object of social management; - thirdly, the professionalization of activities requires a large capital intensity for the formation of professionals; - fourthly, the high efficiency of the activities of professionals in the organization is achieved by creating a rational management of their capabilities.